The NextWave of Expeditious Economic Growth (China, India, Brazil, South Africa and Russia) - Gupta, Shubham (2011)
Being a finance student what amazes me, and should really astound every individual who has the slightest economic sense, is the nature and sheer pace of the changing dynamic of the economies of this world. It will have a profound impact on almost every financial decision made and in fifty years (or even less), the list of the world’s ten largest economies will look very different. The might of United States of America (USA), Japan and Western European countries like Germany and United Kingdom will slowly diminish and pave way for the next surge of dominance in the form of countries like China, India and Brazil. This notion, to my mind, is no longer a matter of opinion but increasingly becoming a matter of fact. It is clear when India grows at around 8% per annum while most industrialized economies contract. It is clear when China manufactures more and more of what the world consumes. It is clear when the President of the USA tells students that ‘you are competing with the kids not only in your own country but in India and China’. This dissertation attempts to highlight this change by reflecting on the many facets of this proposition and giving an overall view of this exciting alteration in the world economy.